Rekontruksi Nilai Transendental sebagai Paradigma Konseling Profetik-Emansipatoris: Dari Normativitas ke Transformasi Sosial - Nur Lana Aprilia; Yatimatul Humairoh; Muhammad Alvin Zailul Hasan; Ali Hasan Siswanto (Indo Publishing, 2026)
The crisis of transcendental values in modern society reflects a tendency to reduce the spiritual-substantive dimension into formal symbolism lacking transformative social power. This condition reveals an imbalance between individual piety and social praxis, as well as the limitations of normative-doctrinal approaches in Islamic Studies, Theology, Philosophy, and Sufism. The research gap lies in the absence of an integrative model capable of operationalizing transcendental values as a methodological foundation for social transformation, particularly within a counseling framework. This study employs a qualitative-conceptual method based on literature review, critical analysis, and philosophical hermeneutics. It integrates the epistemology of transcendental values (tawhid, ihsan, tazkiyatun nafs) with the prophetic paradigm (humanization, liberation, transcendence) within an emancipatory counseling approach. The study argues that transcendental values must be reconstructed both epistemologically and methodologically to function as spiritual and moral capital for just social change. Furthermore, the reinterpretation of amar ma’ruf nahi munkar as a dialogical and transformative counseling process becomes key to bridging the gap between spirituality and social reality. This research contributes by proposing a prophetic-emancipatory counseling paradigm to strengthen social ethics in contemporary society.